The Effect of Liquidity and Capital Structure on Profitability at Pt Siantar Top Tbk 2013-2022 Period - Budhiarjo, Intan Sari; Batubara, Mora Adelina; Cay, Sam (Indonesian Financial Review, 2025)
This study investigates the effect of liquidity and capital structure on profitability at PT Siantar Top Tbk from 2013 to 2022. Using a quantitative approach and multiple regression analysis, liquidity is measured by the current ratio, capital structure by the debt-to-equity ratio, and profitability by the net profit margin. The findings show that liquidity does not have a significant partial effect on profitability, while capital structure has a significant negative impact. However, both variables simultaneously influence profitability significantly. The adjusted R² value of 86.9% indicates that these financial ratios strongly explain changes in profitability. This study highlights the importance of managing debt effectively while optimizing the use of liquid assets. The results provide practical insights for financial decision-making in the consumer goods sector.